STUDI KETERTARIKAN KECOAK JERMAN (Blattella germanica L.) PADA KARBOHIDRAT dari AMPAS TAHU dan AMPAS KELAPA - Az, Syadza Zahratun Nufus; Hariani, Nova; Trimurti, Sus (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Germany cockroaches (Blattella germanica L.) is one of the urban pest that has ability to breeding rapidly. The pest control methods, usually using fogging. However, this method increasing the resistance and environmental damage. So, the new inovation to pest control with bait method. Especially, gel bait is the most widely used method to controlling population of German cockroaches. In making gel bait using glucose aversion behavior that found on German cockroaches. These behavior causing the cockroaches aren’t interested in foods that contain glucose. The solution about behavior is to found another alternative food which is contain high carbohydrate and has abundant sources namely tofu and coconut dregs. This research aims to know the interest of German Cockroaches on tofu dregs and coconut dregs, to find out the total visits of German cockroaches on tofu dregs and coconut dregs, and to find out the relation of the total visits and total food consumption of German Cockroaches. This research using observation method on olfaktometer arena with observation time interval of 15 minutes, 30 minutes, 45 minutes, 60 minutes, and 120 minutes for five days. There are four treatments used in this research namely plain jelly, tofu dregs jelly, coconut dregs jelly, and combination jelly (made from tofu and coconut dregs). The results showed the German cockroaches are more interested in tofu dregs jelly than coconut dregs jelly. Total visits on tofu dregs jelly as much as 330 times and coconut dregs jelly as much as 114 times. The result of regression test showed a positive correlation and correlation between these two variable is significant.